Genome-Scale Mining of Novel Anchor Proteins of Corynebacterium glutamicum - Lin, Kerui; Zhao, Nannan; Cai, Youhua; Lin, Ying; Han, Shuangyan; Zheng, Suiping (Frontiers in Microbiology, 2022)
The display of recombinant proteins on the surfaces of bacteria is a research topic with many possible biotechnology applications. Among which, the choice of host cell and anchoring motif are the keys for efficient display. Corynebacterium glutamicum is a promising host for surface display due to its natural advantages, while single screening methods and fewer anchor proteins restrict its application. In this study, the subcellular localization (SCL) predictor LocateP and tied-mixture hidden Markov models (TMHMM) were used to analyze all five known endogenous anchor proteins of C. glutamicum and test the accuracy of the predictions. Using these two tools, the SCLs of all proteins encoded by the genome of C. glutamicum 13032 were predicted, and fourteen potential anchor proteins were screened. Compared with the positive controls NCgl1221 and NCgl1337, three anchoring proteins NCgl1307, NCgl2775, and NCgl0717 performed better. Using these three anchored proteins to display amylases, their enzyme activities of cell suspension reached 0.34 U/mL(52 U/g dry cells ), 0.41 U/mL(62 U/g dry cells ), and 0.16 U/mL(25 U/g dry cells), respectively. This study also discussed the applicability of the anchor protein screening method used in this experiment to other bacteria.